Kemarahan pada Perempuan Kanker Ginekologi - Yudianti, Alia Isna (Jurnal Keperawatan Soedirman, 2017)
The background of this research is the high rate of gynecology cancer prevalence which influences the psychological effect called maladaptive anger response in women diagnosed with gynecology cancer. The purpose of this research is to identify the representation of anger in women diagnosed with gynecology cancer at one of the hospital in Kota Bandung. This research used a descriptive design which variable is anger in women diagnosed with gynecology cancer. This research involved 50 respondents were taken based on accidental sampling as long as three weeks. The instrument was using STAXI-2 which had already adopted in Indonesia and the validity is 0.85 and the reliability value is 0.89. The data analyzed using mean and serves in a frequencies distribution form.The result showed th at almost all of the respondents (92%) has low state anger, almost all the respondents (94%) has low trait anger, most of respondents (78%) has moderate control out and moderate (84%) control in, and all the respondents (100%) has low index angry expression. Most of the respondents has low intensity of anger, state anger, and also they can’t express their anger adaptively. Respondents prefer push their anger to themselves but in time, anger will appear in a strong enough intensity. Suggested a nurse can develope and give some consultation and therapy to patients diagnosed with gynecology cancer, so they can express their anger in an adaptive way.